A Facile and Rational Method to Tailor the Symmetry of Au@Ag Nanoparticles. Issue 15 (4th March 2023) - Ni, Bing; Zhou, Jian; Stolz, Levin; Cölfen, Helmut
Abstract: Precisely controlling the morphologies of plasmonic metal nanoparticles (NPs) is of great importance for many applications. Here, a facile seed‐mediated growth method is demonstrated that tailors the morphologies of Au@Ag NPs from cubes/cuboids to chiral truncated cuboids/octahedra, well‐defined octahedra, and tetrahedra, via simply increasing the concentrations of AgNO3 and cysteine in the halide surfactant systems. Accordingly, the particle symmetries are also tuned. The method is quite robust where seeds with distinct shapes including irregular ones can all lead to uniform Au@Ag NPs. The evolution of these shapes can be illustrated by a recently proposed symmetry‐based kinematic theory (SBKT). Furthermore, SBKT shows a strategy to optimize the preparation of chiral/dissymmetric NPs, and the experimental results confirm such a dissymmetric synthesis strategy. Cuboids and octahedra with corners differently truncated are identified as two different chiral forms. The chirality of the NPs is additionally probed by electrochemistry, where the chiral NPs show enantioselectivity in the oxidation of d ‐ and l ‐glucose. Altogether, the results gain fundamental insights into tailoring the plasmonic NP morphologies, and also suggest strategies to obtain chiral NPs. Abstract : A facile and rational method to tailor the symmetry of Au@Ag nanoparticles is reported. By introducing l ‐cysteine into the growth system, truncated cuboids/octahedra, well‐defined octahedra, and tetrahedra can be readily obtained with the increase of Ag precursor concentration. Among them, the truncated cuboids/octahedra are chiral, and their formation can be seen as a result of dissymmetric synthesis.